PENGARUH CAPITAL ADEQUACY RATIO (CAR), BOPO, FINANCING TO DEPOSIT RATIO (FDR), DAN NON PERFORMING FINANCING (NPF) TERHADAP RETURN ON ASSET (ROA) BANK SYARIAH (Studi Kasus Pada Bank Umum Syariah yang Terdaftar di OJK Periode 2016-2020) - Sayyidati Mutmainnah; Wirman Wirman (Jurnal Aktual Akuntansi Keuangan Bisnis Terapan (AKUNBISNIS), 2022)
This study has a purpose, namely to find out and analyze the effect of CAR, BOPO, FDR, and NPF on ROA at Islamic Commercial Banks registered with the Financial Services Authority for the 2016-2020 period. The population used in this study were 14 Islamic Commercial Banks and 8 samples were taken using purposive sampling method. The results of the tests that have been carried out are that CAR, BOPO, FDR, and NPF simultaneously have a significant effect on ROA. Meanwhile, for the partial test results, NPF and BOPO have a negative effect on ROA and CAR and FDR have no effect on ROA.